2016
DOI: 10.1177/0269216316661686
|View full text |Cite
|
Sign up to set email alerts
|

Parenting while living with advanced cancer: A qualitative study

Abstract: Background Patients with advanced cancer who have dependent children are an important population with a life-limiting illness and high levels of psychological distress. Few studies have addressed the experience of being a parent with advanced cancer and their potential palliative needs. Aim To describe the experience of living with advanced cancer as a parent, including illness experience, parental concerns, and treatment decision-making and to explore whether these experiences differ by their functional sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
139
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(145 citation statements)
references
References 31 publications
5
139
1
Order By: Relevance
“…Research exploring communication with children about a parental cancer diagnosis has focused on the experiences of parents with advanced cancers (Forrest, Plumb, Ziebland, & Stein, ; Kennedy & Lloyd‐Williams, ; Park et al, ), parents with adolescent children (Huizinga, Visser, van der Graaf, Hoekstra, & Hoekstra‐Weebers, ) and on children's experiences and needs (Ellis, Wakefield, Antill, Burns, & Patterson, ; Furlong, ; Thastum, Johansen, Gubba, Olesen, & Romer, ). There has been little research on parents’ communication with younger children (Furlong, ) or the needs of parents with younger children when the parent is diagnosed with cancer treated with curative intent.…”
Section: Introductionmentioning
confidence: 99%
“…Research exploring communication with children about a parental cancer diagnosis has focused on the experiences of parents with advanced cancers (Forrest, Plumb, Ziebland, & Stein, ; Kennedy & Lloyd‐Williams, ; Park et al, ), parents with adolescent children (Huizinga, Visser, van der Graaf, Hoekstra, & Hoekstra‐Weebers, ) and on children's experiences and needs (Ellis, Wakefield, Antill, Burns, & Patterson, ; Furlong, ; Thastum, Johansen, Gubba, Olesen, & Romer, ). There has been little research on parents’ communication with younger children (Furlong, ) or the needs of parents with younger children when the parent is diagnosed with cancer treated with curative intent.…”
Section: Introductionmentioning
confidence: 99%
“…Studies also show that maximising time spent with children and preserving a role as a parent are important concerns underlying patients’ preferences (Check et al, ; Zaider, Sally, Terry, & Davidovits, ). Such patients are concerned about how to maintain parental responsibilities and how their illness and death will impact on their children (Park et al, ). Patients with parental responsibility struggle to balance their roles as a parent with being a seriously ill patient, agonising, for example, about whether to spend time with their children or to rest to combat their illness (Bell & Ristovski‐Slijepcevic, ; Morris, Martini, & Preen, ).…”
Section: Introductionmentioning
confidence: 99%
“…Seriously ill patients with parental responsibility experience an increased level of psychosocial distress, major depressive disorder and generalised anxiety compared to peers (Muriel et al, 2012;Park et al, 2016). Patients with parental responsibility tend to make more aggressive treatment decisions, including receiving highly toxic treatment, and less often initiate advance care planning, write "donot-resuscitate" (DNR) orders or leave a living will (Nilsson et al, 2009;Park et al, 2017;Yellen & Cella, 1995).…”
mentioning
confidence: 99%
“…Individuals with advanced cancer who have dependent children experience unique challenges to their health‐related quality of life (HRQOL) and psychological functioning. They have parenting concerns about the current and future impact of their illness on their children, uncertainty regarding optimal illness‐related communication with their children, and profound anguish that they may not raise their children into adulthood . Cross‐sectional studies have suggested that parents with advanced cancer have high rates of anxiety and depressive symptoms, and higher rates of mood disorders in comparison with patients without dependent children …”
Section: Introductionmentioning
confidence: 99%
“…They have parenting concerns about the current and future impact of their illness on their children, 4,5 uncertainty regarding optimal illness-related communication with their children, 5 and profound anguish that they may not raise their children into adulthood. [5][6][7] Cross-sectional studies have suggested that parents with advanced cancer have high rates of anxiety and depressive symptoms, 4,8 and higher rates of mood disorders in comparison with patients without dependent children. 9 Parenting concerns also may influence cancer treatment decision making.…”
Section: Introductionmentioning
confidence: 99%